Researching monumental spaces in late prehistoric societies: New perspectives for landscape research in the Russian Altai. (September 2018) - Vergauwe, Ruben; Bourgeois, Jean; Gheyle, Wouter
Abstract: In this article we present a preliminary study discussing new perspectives for future research and interpretation of the Bronze and Iron Age monuments and monumental landscapes in terms of their social dynamic in these early complex societies. Archaeological landscape research in the last decades is characterized by a significant paradigmatic separation, resulting in often one-dimensional treatments of landscapes. Using certain concepts developed by Henri Lefebvre and Martina Löw, we address social landscape as a three-dimensional social space, which enabled us to integrate multiple approaches. This triadic framework is discussed using a case study which focuses on data of the Karakol and Yustyd valley in the Russian Altai. Our study shows that the general transitions in the use and structure of monuments during the late Bronze Age and early Iron Age can be variously interpreted. These interpretations are not necessarily exclusive but may each reflect a partial rendition of the triadic model of social space, or monumental space .